Making Contextual Teaching Module Based on Independent Curriculum for Primary School Teachers - Erikson Simbolon; Paulinus Tibo; Paulus Halek Bere (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Teaching modules are tools for teachers to implement learning. The preparation of teaching modules requires teachers to hone their high-level thinking skills to be able to innovate in the preparation of teaching modules according to context. So the preparation of teaching modules is the application of the teacher's pedagogic competence so that the technique of implementing learning in the classroom is effective and in accordance with the indicators of learning objectives. The purpose of this activity is to carry out training in writing contextual teaching modules for Catholic religion subjects for PAK teachers at the elementary school level in Karo Regency. To achieve these training objectives, this community service activity is packaged in five sessions, namely: 1. training socialization; 2. explanation of the concept of teaching modules for elementary school Catholic religious education; 3. training on the preparation of teaching modules; 4. practice of preparing teaching modules for elementary school teachers; and 5. evaluation of the implementation of teaching module preparation training to determine the development of teachers' abilities. The implementation of this teaching module preparation training activity involves giving participants' opinions on the systematic preparation of teaching modules. The target of this training activity is that teachers who teach Catholic religion subjects at the Karo Regency Elementary School level are able to develop context-based independent curriculum teaching modules that are in accordance with the needs of students. Overall, all training sessions for Catholic religious education teachers at the elementary school level in the Karo district went well, and the teachers followed them with great enthusiasm.